Rekonstruksi dan Reaktualisasi Literasi Ekologi Sosial Islam - Heru Kurniawan (Jurnal Penelitian, 2016)
Literacy on Islamic social ecology is the human interaction with the natural environment, technology, and social which is based on the basic principles of Islam. Reconstruction of literacy on Islamic social ecology that can be reconstructed is a basic tenet of Islam that affirms the human position as a "leader" by "mandate" to manage "Earth" or "natural environment and natural resources" as well as possible. Reconstruction of ecological literacy is then to be actualized in society. The process of actualization is actual activity in instilling awareness of the social ecology of Islam in the society which is done in the social space of families, communities, and schools organized by the state through policies and regulations. With the process of reconstruction and actualization, then the state will actively build social-ecological awareness of Islam in order to realize a base of awareness, knowledge, and values of Islamic social ecology in society.